Research and action agenda for a national broadband initiative in India - Rekha Jain; Rajanish Dass (International Telecommunications Society (ITS), 2011)
Broadband has found to have substantial impact on the economic growth of various nations. Recognizing the positive impact of broadband, several countries have gone ahead with their respective broadband plans, which, at times, include requisite fiscal stimulus. In this paper we have tried to look into several of these international examples and have tried to put forth the challenges and opportunities that exist in a fast developing country like India. Based on these experiences, observations and analysis, this paper tries to bring forth recommendations towards a National Broadband Policy for India and suggests the objectives and structure of the same - thus setting a research and policy agenda for the nation. The findings of this paper may also provide necessary inputs to policy makers of such developing nations to formulate a similar broadband policy and management organization for them.
Keywords: 330